Analysis of Stock Mutual Fund in Indonesian Economy - Victor Siagian (Business and Entrepreneurial Review, 2005)
Mutual Fund is one of developing industries. Since it was launched in 1996, mutual fund industry has repidly grown. This fact was indicated by more and more mutual funds that are operated. This condition provides more choices for by investors. Beside considering of benefit and value which will be given by mutual fund, investors must also consider performance of mutual fund. The objective of this research is to evaluate performance of mutual fund in Indonesia and what factors which influence the performance of mutual fund. Measure the performance of the mutual fund, this research used model awhich was developed by Alpha Jensen. Using Jensen model caused an unconditional model, which performance of mutual fund can be compared without focusing on the differentiation of the portfolio diversification level. This model measures performance by intercept of regression between excess portfolioreturn as dependent variable and excess market return as independent variable. The result of this research that is only two of six mutual fund has outperform toward market perform as a benchmark performance. Variable of excess market retum level was consistent influenced portfolio return with positive significance. The bad mutual fund performance more caused by stocks election ability of portfolio managers in selectingaccurate stock to porlfolio. Beside uncapability of portfolio managers in selecting accurate stock, the different characteristic of mutual fund caused bad observed mutual fund.